Absorption of prednisolone in patients with Crohn's disease. Issue 3 (March 1983) - Shaffer, J A; Williams, S E; Turnberg, L A; Houston, J B; Rowland, M
Abstract : The absorption of prednisolone in patients with Crohn's disease was investigated. Seven patients with Crohn's disease and eight normal control subjects were given a tracer dose of tritiated prednisolone with 20 mg cold prednisolone by mouth. On a separate occasion they were given an intravenous injection of radiolabelled prednisolone. After oral ingestion only 53.4 +/- 11.7% of labelled material was excreted in the urine of Crohn's patients compared with 82.5 +/- 3.6% in the normal subjects. The oral/intravenous availability ratio was 0.61 +/- 0.14 in Crohn's patients and 0.89 +/- 0.07 in the normal group. Areas under plasma concentration-time curves were lower in patients than normal subjects and the oral/intravenous ratios were 0.6 +/- 0.2 and 0.86 +/- 0.09 respectively. Faecal excretion of radioactivity after oral ingestion was greater in Crohn's patients (19.3 +/- 2.5%, n = 3) than in normal subjects (7 +/- 2.8%, n = 4). The range for each type of measurement was much wider in the patient group than in the normal subjects. These data suggest that patients with Crohn's disease do not absorb prednisolone normally and that absorption varies between patients.